Clash of Career and Family: Fertility Decisions after Job Displacement - Emilia Del Bono; Andrea Weber; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2008)
In this paper we investigate how fertility decisions respond to unex- pected career interruptions which occur as a consequence of job displace- ment. Using an event study approach we compare the birth rates of dis- placed women with those of women una®ected by job loss after establish- ing the pre-displacement comparability of these groups. Our results reveal that job displacement reduces average fertility by 5 to 10% in both the short and medium term (3 and 6 years) and that these e®ects are largely explained by the response of white collar women. Using an instrumen- tal variable approach we provide evidence that the reduction in fertility is not due to the income loss generated by unemployment but arises be- cause displaced workers undergo a career interruption. These results are interpreted in the light of a model in which the rate of human capital accumulation slows down after the birth of a child and all specific human capital is destroyed upon job loss.
Keywords: J13; J64; J65; J24; 330; fertility; unemployment; plant closings; human capital; Frauenarbeitslosigkeit; Fruchtbarkeit; Erwerbsverlauf; Humankapital; Liquidation; Familienpolitik; Österreich